Spinal anesthesia during foot surgery - Gritsenko, S. N.; Filimonova, І. V.; Filimonov, R. V. (Modern medical technology, 2021)
Purpose of the study. To improve the results of treatment of patients with diabetic foot syndrome by substantiating the optimal type of spinal anesthesia during foot surgery. Materials and methods. 70 patients undergoing treatment in the department of purulent surgery were examined. Patient groups: Group 1 – patients operated on under conditions of unilateral spinal anesthesia; Group 2 – patients operated on under traditional spinal anesthesia. Research methods. Assessment of the level and intensity of pain, concentration of catecholamines in urine in the first postoperative day, monitoring of blood pressure (BP), heart rate (HR), peripheral blood oxygen saturation (SpO2), Doppler scanning of peripheral blood flow in the foot, skin temperature integument of the foot during anesthesia and statistical. Results. In group 1, pain sensitivity during movement of the lower limb after anesthesia was 21% less pronounced than in group 2. In group 2, the heart rate decreased by 4,8% during anesthesia. The SpO2 level 20 minutes after the onset of anesthesia decreased in group 2 by 5,1% compared to group 1. The mean arterial pressure in group 2 decreased during anesthesia by 9,9%, in contrast to patients in group 1. After performing anesthesia, systolic blood pressure in the toe increased by 18,3%, and the temperature of the skin on the lateral surface of the leg increased by 3,7%. The concentration of adrenaline in the daily portion of urine in the next postoperative day in group 2 is 35,1% higher than in group 1. Conclusions. During anesthesia, the blood pressure, heart rate and SpO2 in group 1 did not change in comparison with the initial values (on the operating table before anesthesia). After anesthesia, an improvement in peripheral blood flow in the operated limb was noted. Unilateral spinal anesthesia, in comparison with traditional spinal anesthesia, has a positive effect on the stress response of the patient's body to surgery.